Reductive Deposition of Thin Cu Films Using Ballistic Hot Electrons as a Printing Beam. Issue 6 (1st January 2016) - Suda, R.; Yagi, M.; Kojima, A.; Mori, N.; Shirakashi, J.; Koshida, N.
Abstract : Alternative deposition of thin solid films is demonstrated using a nanocrystalline silicon ballistic electron emitter. Emitted ballistic hot electrons impinge upon a CuCl2 -solution-coated Si substrate that is located in proximity close to the emitter. It is shown from spectroscopic characterizations that thin Cu films are deposited onto the target substrate with no contaminations. As-emitted ballistic hot electrons with energies of 5–7 eV promote preferential reduction of Cu 2+ ions within the penetration depth in the solution followed by the nuclei formation for growth of thin film. The presented printing scheme is also available for oxidized Si substrates. The direct reduction model is supported separately by cyclic voltammetry analyses on the reducing activity of ballistic electrons.